2006
DOI: 10.1002/glia.20405
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor and its p55 and p75 receptors are not required for axonal lesion‐induced microgliosis in mouse fascia dentata

Abstract: Tumor necrosis factor (TNF) is a potent pro-inflammatory and neuromodulatory cytokine. In the CNS it is produced primarily by microglia and considered to regulate microglial activation. On the basis of previous observations of increased microglial TNF mRNA synthesis in areas of anterograde axonal and terminal degeneration in mice, we studied the effect of TNF and its p55 and p75 receptors on axonal lesion-induced microglial activation in fascia dentata following transection of the perforant path (PP) projectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
3
12
2
Order By: Relevance
“…This was partly attributable to our finding of comparable neocortical volumes and CD11b mRNA levels and partly because we, despite reports about a stimulatory role of TNF on microglial proliferation in vitro (Théry and Mallat, 1993), failed to observe significant differences in microglial numbers in both unmanipulated hippocampus and perforant pathway-deafferented dentate gyrus in TNF-KO, TNFp55Rp75R-KO, TNF-p55R-KO, and WT mice (Babcock et al, 2006;Fenger et al, 2006). Although undetectable in the volumetric data in this study, and in conventional microglial stainings, we cannot exclude that the cellular composition and fine structure of neocortex may differ between TNF-KO and WT mice, or that there are regional adjustments of microglia as a result of different homeostatic requirements by cortical and hippocampal neurons.…”
Section: Discussioncontrasting
confidence: 64%
“…This was partly attributable to our finding of comparable neocortical volumes and CD11b mRNA levels and partly because we, despite reports about a stimulatory role of TNF on microglial proliferation in vitro (Théry and Mallat, 1993), failed to observe significant differences in microglial numbers in both unmanipulated hippocampus and perforant pathway-deafferented dentate gyrus in TNF-KO, TNFp55Rp75R-KO, TNF-p55R-KO, and WT mice (Babcock et al, 2006;Fenger et al, 2006). Although undetectable in the volumetric data in this study, and in conventional microglial stainings, we cannot exclude that the cellular composition and fine structure of neocortex may differ between TNF-KO and WT mice, or that there are regional adjustments of microglia as a result of different homeostatic requirements by cortical and hippocampal neurons.…”
Section: Discussioncontrasting
confidence: 64%
“…43 In the CNS, TNF is expressed primarily by microglia or infiltrating macrophages in response to injury, 96 and is induced by inflammatory cytokines such as IFN-␥ 97 or by cell-cell contact with activated myelin-reactive T cells. 98,99 Using the PP lesion model, our group has previously demonstrated a transient increase in TNF mRNA expression levels at 2 days post lesion, 34 which was increased by the presence of IFN-␥. 100 This was confirmed in the present study, in which a marked increase in TNF mRNA expression was observed in T PLP mice at 2 days post lesion and persisted at 7 days post lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were rinsed and incubated using monoclonal rat anti-BrdU antibody (AB6326; dilution 1:100; Abcam Ltd., Cambridge, England), which was detected using biotinylated goat anti-rat Ig antibody (RPN 1005; dilution 1:200; Amersham Pharmacia Biotech, Inc.), and alkaline phosphatase-conjugated streptavidin (P396; Dako A/S), and incubated in an alkaline phosphatase developer as previously described. 34 …”
Section: Diaminobenzidine/alkaline Phosphatase Double Immunohistochemmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the present study show that such pathogens may be also produced by dead medulloblastoma cells. The role of TLRs in pathology of the CNS was a subject of numerous studies, which documented the implication of TLR 2 signalling in glia responses associated with repair by the clearance of myelin debris [6,9,10].…”
Section: O -Lack Of Antigen In Tissue Sections; + -< 10%; ++ -25-40%;mentioning
confidence: 99%